2012
DOI: 10.1142/s0217751x12501618
|View full text |Cite
|
Sign up to set email alerts
|

POSSIBLE $D\bar{D}$ AND $B\bar{B}$ MOLECULAR STATES IN A CHIRAL QUARK MODEL

Abstract: We perform a systematic study of the bound state problem of [Formula: see text] and [Formula: see text] systems by using effective interaction in our chiral quark model. Our results show that both the interactions of [Formula: see text] and [Formula: see text] states are attractive, which consequently result in [Formula: see text] and [Formula: see text] bound states.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 20 publications
6
26
0
Order By: Relevance
“…[3] it was shown that the bump was better interpreted in terms of a DD molecular state, below the DD threshold (so called X(3700)), that had been predicted in Ref. [4] and has also been found theoretically in other works [5][6][7][8][9]. Similarly, in Ref.…”
Section: Introductionsupporting
confidence: 52%
“…[3] it was shown that the bump was better interpreted in terms of a DD molecular state, below the DD threshold (so called X(3700)), that had been predicted in Ref. [4] and has also been found theoretically in other works [5][6][7][8][9]. Similarly, in Ref.…”
Section: Introductionsupporting
confidence: 52%
“…In this sense, a bound state of DD was theoretically found in [6] and tentatively called X(3700). Other works have also reported on this possibility [7][8][9][10][11][12]. Subsequently, experimental support for such a state was found in [13] from a bump close to the threshold of the DD invariant mass distribution in the e + e → J/ψDD reaction [14].…”
Section: Introductionmentioning
confidence: 92%
“…The work on the charm sector is gradually moving to the beauty sector and there are works dealing with b or hidden b meson molecules built up from other mesons containing some b quark [17][18][19][20][21][22][23][24]. The recent discovery of the hidden beauty Z b (10610) and Z b (10650) states in three charge states [25][26][27], and hence with isospin I=1, has brought a new stimulus to the molecular idea [20,21,23], since they cannot be bb quarkonium states.…”
Section: Introductionmentioning
confidence: 99%